Business culture impairs facial trustworthiness judgments - Zhang, Hongchuan; Liu, Yitong; Li, Weiran; Nie, Mengjie; Xin, Ziqiang (Frontiers in Psychology, 2024)
Previous research has found that business culture has a detrimental impact on interpersonal trust. To understand whether this impact extends to rapid, automatic, bottom–up judgments of facial trustworthiness, we conducted 4 experiments involving 244 participants from economic and non-economic backgrounds. We presented participants with both trustworthy and untrustworthy faces and asked them to make judgments on trustworthiness. The results show that individuals who are engaged in studying economics, work in an economics-related occupation, or are exposed to an imagined business culture evaluate trustworthy faces to be less trustworthy. The findings shed light on why and how business culture affects the formation of interpersonal trust.